2017
DOI: 10.1108/ribs-04-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Inward retail internationalization and exogenous – based outshopping on the US-Mexico border

Abstract: Purpose Previous research on the internationalization of retailing typically focused on retail companies crossing borders to enter other countries. Yet, a large number of people cross country borders to outshop in neighboring countries. This form of inward retail internationalization has received little attention in the literature. To address this void, the purpose of this paper is to investigate the strategies of retailers in a border zone setting. Design/methodology/approach The authors collected data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It encompasses activities like cross-border shopping, parallel trade, and international out-shopping (Sharma et al 2018). Extensive research has been conducted globally to understand the reasons behind cross-border shopping tourism, including for the borders between Canada and the US, various European countries, Malaysia and Singapore, Mainland China and Hong Kong, Germany and Denmark, Mexico and the US, and Thailand and Laos (Piron 2002;Baruca and Zolfagharian 2012;Lau et al 2005;Nguyen et al 2016;Makkonen 2016;Hadjimarcou et al 2017;Boonchai and Freathy 2020). One common motivation for engaging in cross-border shopping tourism is the opportunity to benefit from differences in taxes and/or product quality (UNWTO 2014).…”
Section: The Impacts Of Tourism On Retail Marketsmentioning
confidence: 99%
“…It encompasses activities like cross-border shopping, parallel trade, and international out-shopping (Sharma et al 2018). Extensive research has been conducted globally to understand the reasons behind cross-border shopping tourism, including for the borders between Canada and the US, various European countries, Malaysia and Singapore, Mainland China and Hong Kong, Germany and Denmark, Mexico and the US, and Thailand and Laos (Piron 2002;Baruca and Zolfagharian 2012;Lau et al 2005;Nguyen et al 2016;Makkonen 2016;Hadjimarcou et al 2017;Boonchai and Freathy 2020). One common motivation for engaging in cross-border shopping tourism is the opportunity to benefit from differences in taxes and/or product quality (UNWTO 2014).…”
Section: The Impacts Of Tourism On Retail Marketsmentioning
confidence: 99%
“…Timothy and Tosun (2003) claimed that cross-border tourism between neighbouring states is relatively unexplored in the literature, Another special type of cross-border shopping is seen as "parallel trading activities" such as Chinese cross-border tourists to Hong Kong carrying products from Hong Kong to Mainland China for resale (Li, Cheung, & Han, 2018). More importantly, two recent tourism studies (Hadjimarcou, Herrera, & Salazar, 2017;Sharma, Chen, & Luk, 2018) claimed that cross-border tourists contributed equally to the internationalisation of trade. In addition, Hampton (2010) proposed that cross-border as a form of economic development, which suggested that cross-border tourism generated income, employments, and economic linkages for the analysis of cross-border tourism between Indonesia, Malaysia, and Singapore.…”
Section: Literature Reviewmentioning
confidence: 99%